Geoelectromagnetic field in the shoreline region according to physical modelling - V. M. Kobzova; V. Yu. Maksymchuk; B. T. Ladanivskiy; P. K. Martyuk; R. B. Dutko (Ukrainian Antarctic Journal, 2008)
The analog modeling method with usage of special laboratory installation was applied for direct electrodynamics problem of three-layered environment with local 3D conductance inhomogeneity. It is shown that anomalous geomagnetic fields created by the local coast structures (cape, bay, islands near continent) should be taken into account for 2D magnetotelluric data inversion. The coast effect caused by complex shape of coastline unlike linear one could be as a large hindrance for deep MT sounding on coast estimation of depth of high-conductive mantle could be reduced.